2015
DOI: 10.1590/s0104-12902015127606
|View full text |Cite
|
Sign up to set email alerts
|

Representações sociais sobre o acesso e o cuidado pré-natal no Sistema Único de Saúde da Região Metropolitana da Grande Vitória, Espírito Santo

Abstract: ResumoAs representações sociais das puérperas sobre o acesso ao cuidado pré-natal destacam aspectos relacionados às barreiras de acesso e às formas de sua superação. O objetivo deste trabalho foi analisar o acesso ao cuidado pré-natal a partir das representações sociais de usuárias do Sistema Único de Saúde. A partir de 1.035 puérperas, selecionaram-se 24 puérperas da Região Metropolitana da Grande Vitória, Espírito Santo: um grupo de 14 puérperas que realizou mais de seis consultas de pré-natal e um grupo de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
23

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 17 publications
0
17
0
23
Order By: Relevance
“…Six of the analysed studies identified the limited resources in Health that prevent the doctrinal and organisational principles of the SUS from taking place in the users' daily life (Degli Esposti et al, 2015;Santos Neto et al, 2012;Pimentel et al, 2012& Almeida & Tanaka, 2009). The pregnant women reported they took tests in private institutions to ensure the results were available before the appointment.…”
Section: Insufficient Quotas For Primary Healthcare Screeningsmentioning
confidence: 99%
“…Six of the analysed studies identified the limited resources in Health that prevent the doctrinal and organisational principles of the SUS from taking place in the users' daily life (Degli Esposti et al, 2015;Santos Neto et al, 2012;Pimentel et al, 2012& Almeida & Tanaka, 2009). The pregnant women reported they took tests in private institutions to ensure the results were available before the appointment.…”
Section: Insufficient Quotas For Primary Healthcare Screeningsmentioning
confidence: 99%
“…Six of the analysed studies identified the limited resources in Health that prevent the doctrinal and organisational principles of the SUS from taking place in the users' daily life (Degli Esposti et al, 2015;& Almeida & Tanaka, 2009. The pregnant women reported they took tests in private institutions to ensure the results were available before the appointment.…”
Section: Insufficient Quotas For Primary Healthcare Screeningsmentioning
confidence: 99%
“…Os recursos limitados na saúde que impedem que os princípios doutrinários e organizativos do SUS se efetivem no dia-a-dia dos usuários foram identificados em seis estudos analisados (Degli Esposti et al, 2015;& Almeida & Tanaka, 2009. As gestantes relataram a realização de exames em instituições privadas, para garantir que os resultados estivessem disponíveis para a consulta.…”
Section: Quotas Insuficientes Dos Exames Para a Atenção Primária à Saúdeunclassified
“…The perspective of the agents who build lives in the HS -managers, providers, professionals and users -is fundamental to understanding the problems related to access and the possible strategies to confront it (Esposti et al, 2015), especially in the case of the adolescent population that makes little use of these services. In this study, this perspective will be explored through discourse, since it contributes to the construction of social identities and positions of subjects; social relations among people; and knowledge and belief systems (Fairclough, 2001).…”
Section: Introductionmentioning
confidence: 99%